"The Numbers Are Eye Popping": Statistical Consciousness as a Discursive Tool to Monitor Same-Sex Demography. (February 2022) - Walther, Carol S.; Jones, Stephanie D.; Wickens, Corrine M.; Martinez, Rodrigo
In this article, we examine newspaper accounts of same-sex demography to examine how journalists use U.S. Census Bureau statistics to discuss changes in lesbian and gay households from 1990 to 2015. We utilized Foucault's discussion of discourse and discussed what we call statistical consciousness, the use of statistics in everyday life. We support these findings with qualitative examples of each same-sex household increase to show how journalists present statistical data to exaggerate or misrepresent the number of same-sex households in the United States. We argue that the journalists use dramatic and exaggerated descriptors to characterize and frame U.S. Census Bureau statistics regarding same-sex demography. The dramatic and exaggerated reports of same-sex demography influence how people think about Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ+) people and the census.